From Deficiency to Difference: A Critical Phenomenological Approach to Autistic Ways of Being - Lee, Tiffany (The Stellenbosch Socratic Journal, 2025)
Throughout the history of Autism research, Autistic lived experiences have been pathologised — seen as lacking in the fundamental structures which shape human lived experience. Only recently, with the rise of the neurodiversity movement to mainstream prominence, has a critical lens been taken to Autism research. This paper argues that classical phenomenology is an inadequate framework for understanding the subjective lived experiences of Autistic individuals. While classical phenomenology provides methodological foundations for understanding subjective lived experiences, it often overlooks the social structures that shape certain lived realities. Thus, I will contend that a critical phenomenological lens must be applied to future Autism research for the Autistic lived experience to be accurately and justly understood as a facet of diverse human existence rather than a demonstration of existential lack. Drawing on the arguments of Davis (2020), Guenther (2020), and Gordon (2020), I will distinguish critical phenomenology from classical phenomenology, exploring how it intentionally addresses the gaps in the classical framework. These arguments demonstrate how classical phenomenology's universalist assumptions fail to capture Autistic lived experiences across multiple domains — from alternative temporal structures and attention patterns to different sensory processing and meaning-making capacities — reducing neurological diversity to pathological deficiency. Ultimately, this paper will argue that critical phenomenology is essential for future Autism research to acknowledge human diversity, abandon pathologising approaches, and centre Autistic subjectivity.